Korelasi Pola Makan dengan Siklus Menstruasi pada Remaja di Sekolah Menengah Pertama Mataram Kasihan - Nazihah; Lutfiyati, Afi (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Menstruation is a natural biological process in women that involves the shedding of the uterine lining through the vagina. This bleeding occurs periodically, separated by intervals known as the menstrual cycle. Various factors can lead to irregularities in this cycle, with diet being one of the key contributors. A diet refers to the planned intake of food types and quantities intended to support health, fulfill nutritional needs, and aid in disease prevention or recovery. Objective: This study aims to examine the relationship between dietary habits and the menstrual cycle among female adolescents at SMP Mataram Kasihan. Methods: The research was carried out at Mataram Kasihan Junior High School, located in Bantul Regency, Yogyakarta, from February to October 2024. It employed a quantitative method with a prospective cohort design, which evaluates the correlation between independent and dependent variables over a specific time period. Quota sampling was utilized to select 43 respondents. A questionnaire was used to collect data on dietary patterns and menstrual cycles, and analysis was performed using the Chi-square test. Results: Findings revealed that 23 participants (53.5%) followed an unhealthy diet, while 22 participants (51.2%) experienced abnormal menstrual cycles. Statistical analysis yielded a p-value of 0.327, indicating no significant relationship (p > 0.05). Conclusion: The study concludes that there is no statistically significant association between dietary patterns and menstrual cycle regularity among adolescents at SMP Mataram Kasihan.